Structure‐Performance Relationship of LaFe1‐xCoxO3 Electrocatalysts for Oxygen Evolution, Isopropanol Oxidation, and Glycerol Oxidation. Issue 4 (17th February 2022) - Brix, Ann Cathrin; Dreyer, Maik; Koul, Adarsh; Krebs, Moritz; Rabe, Anna; Hagemann, Ulrich; Varhade, Swapnil; Andronescu, Corina; Behrens, Malte; Schuhmann, Wolfgang; Morales, Dulce M.
Abstract: Mitigating high energy costs related to sustainable H2 production via water electrolysis is important to make this process commercially viable. Possible approaches are the investigation of low‐cost, highly active oxygen evolution reaction (OER) catalysts and the exploration of alternative anode reactions, such as the electrocatalytic isopropanol oxidation reaction (iPOR) or the glycerol oxidation reaction (GOR), offering the possibility of simultaneously lowering the anodic overpotential and generating value‐added products. A suitable class of catalysts are non‐noble metal‐based perovskites with the general formula ABO3, featuring rare‐earth metal cations at the A‐ and transition metals at the B‐site. We synthesised a series of LaFe1‐x Cox O3 materials with x=0–0.70 by automated co‐precipitation at constant pH and subsequent calcination at 800 °C. X‐ray diffraction studies revealed that the phase purity was preserved in samples with x≤0.3. The activity towards the OER, iPOR, and GOR was investigated by rotating disk electrode voltammetry, showing a relation between structure and metal composition with the activity trends observed for the three reactions. Additionally, GOR product analysis via high‐performance liquid chromatography (HPLC) was conducted after 24 and 48 h electrolysis in a circular flow‐through cell setup, pointing out a trade‐off between activity and selectivity. Abstract : Energy saving : Sustainable H2 production via water electrolysis can be made possible by mitigating high energy costs through the thorough investigation of low‐cost materials for the oxygen evolution reaction (OER) but also oxidation of alcohols, such as isopropanol and glycerol, as they offer possible lower overpotentials and valuable product generation. Thus, the impact of Co incorporation in LaFeO3 perovskites on structure, activity, and glucose oxidation reaction (GOR) selectivity is studied.